Nation building: education for elites: a case study of residential secondary schools in Malaysia - Ismail, Nik Ahmad Hisham (VDM Verlag Dr. Muller GmbH & Co. KG, 2011)
Education for Elites addresses the aspiration of the government in providing education for the future ethnic Malays leaders in Malaysia. The focus of the book is on the development of an "an elite education" for the ethnic Malays. In addition, the ethnic Malays' perceptions toward leadership will also be highlighted in the book. Indeed, and it is well observed that the struggle for the survival of the ethnic Malays since independence has become an important agenda for the government. Ever since,the government has acted as the catalyst and expected to become an important player for modernizing and developing the ethnic Malays. Thus,the perceptions of the ethnic Malay students toward leadership show the importance of education and leadership which are aligned with the aspirations of the government.